IMPLEMENTATION OF THE INTEGRATED ENTREPRENEURSHIP DEVELOPMENT POLICY IN IMPROVING MICRO AND SMALL ENTERPRISES IN SOUTH JAKARTA: Administrasi Publik - Ramzy Muhammad Ramzy Alfaridzy; Tri Yuniningsih; Rizky Hidayati; Sekar Arum Arjun Syarifah; Young-hoon Ahn (Institut Riset dan Pengembangan Indonesia, 2026)
The low number of entrepreneurs and the suboptimal contribution of micro and small businesses in South Jakarta, as reflected in the fluctuation in the number of micro and small industries in the 2021–2023 period, indicate problems in the implementation of integrated entrepreneurship development policies. South Jakarta has great economic potential and a high number of productive-age residents, with the highest allocation of integrated entrepreneurship participants in DKI Jakarta at 67,208 participants. This study uses a qualitative descriptive method. Data collection was carried out through in-depth interviews, observation, and documentation studies. Data analysis in this study was conducted using policy implementation theory. The results of this study show that the integrated entrepreneurship development policy has been implemented but has not been fully implemented in developing entrepreneurial potential and creating new business actors. Policy implementation has not been optimal due to limited resources, suboptimal coordination between regional agencies, and limited follow-up support for business actors, especially in terms of ongoing assistance with capital and marketing. Based on these findings, it is recommended that coordination between regional agencies be strengthened, the availability and capacity of mentors be increased, and support for training and marketing be strengthened so that the performance of micro and small businesses can improve optimally and sustainably.